Lysyl oxidase expression is associated with inferior outcome and Extramedullary disease of acute myeloid leukemia - Desiree Kunadt; Michael Kramer; Claudia Dill; Heidi Altmann; Lisa Wagenführ; Brigitte Mohr; Christian Thiede; Christoph Röllig; Johannes Schetelig; Martin Bornhäuser; Markus Schaich; Friedrich Stölzel (Biomarker Research, 2020)
Abstract Background Lysyl oxidase (LOX) has been described as necessary for premetastatic niche formation in epithelium-derived malignancies and its expression level therefore correlates with risk of metastatic disease and overall survival. However, its role in acute myeloid leukemia (AML) has not been sufficiently analyzed. Methods We investigated LOX plasma expression in 683 AML patients (age 17–60 years) treated within the prospective AML2003 trial (NCT00180102). The optimal cut-off LOX value was determined using a minimal-p-value method dichotomizing patients into a LOX-high group (> 109 ng/mL, n = 272, 40%) and a LOX-low group (≤ 109 ng/mL, n = 411, 60%). Results Higher LOX expression was associated with lower peripheral white blood cells, lower serum LDH, and a lower frequency of FLT3-ITD and NPM1 mutations at diagnosis. Higher LOX expression was found significantly more frequently in patients with secondary AML and therapy-related AML, in patients with French-American-British M5 subtypes, and in patients with adverse-risk cytogenetics. Comparing patients in the LOX-high group and the LOX-low group revealed a 3-year overall survival (OS) of 47 and 53% (p = 0.022) and 3-year event-free survival (EFS) of 27 and 35% (p = 0.005), respectively. In the LOX-high group significantly more patients had extramedullary AML compared to the LOX-low group (p = 0.037). Combining extramedullary AML and LOX as interacting factors in a multivariate analysis resulted in an independent impact on survival for the LOX-high-extramedullary interaction for OS (HR = 2.25, p = 0.025) and EFS (HR = 2.48, p = 0.008). Furthermore, in patients with extramedullary disease (n = 59) the LOX level predicted survival. Patients within the LOX-low group had an OS of 43% and EFS of 36% as compared to the LOX-high group with an OS of 13% and EFS of 6% (p = 0.002 and p = 0.008, respectively). Conclusion We hypothesize LOX expression to be a new potential biomarker to predict outcome in AML, specifically in AML subgroups such as the prognostic heterogeneous group of AML patients with extramedullary disease. Trial registration This retrospective study was performed with patient samples registered within the prospective AML2003 trial ( NCT00180102 ). Patients were enrolled between December 2003 and November 2009.